“[My] soft, smooth skin… cut deep”: Using Filmmaking to Imagine, Feel and Perform Colonial Natural History in the Museum - Everest, Sophie Florence (Museum and Society, 2024)
Museums internationally continue to engage in urgent debates about the need to decentre the epistemological foundations of collections and institutions built on colonial expansion. Industrial cities like Manchester are only just beginning to address the uncomfortable legacies of colonial exploitation within their educational and cultural institutions. Contributing to this discussion, this article examines a project at the Manchester Museum that invited students from a local school to collaborate in the production of a film inspired by taxidermy specimens originating from a 1929 hunting safari in Sudan. Recounting the methods and outputs of this practice-based research project, I suggest that a cross-collections, creative approach to engaging audiences can generate new forms of imaginative and performed knowledge about the colonial histories of collections. Not only can these new forms of knowledge challenge existing accounts of provenance, they can be a tool to address historical injustices: inviting audiences to re-tell the histories of these things in their own words and making permanent space for these creative outputs within collections.